The Impact of EU Politicisation on Voting Behaviour in Europe - Costa Lobo, Marina (Palgrave Studies in European Union Politics, 2023)
This open access book focuses on the importance that EU politicization has gained in European democracies and the consequences for voting behaviour in six countries of the EU: Belgium, Germany, Greece, Ireland, Portugal and Spain. Most of the studies which research the way the EU is being legitimised focus on the European Parliament elections. In this book we argue that to understand how EU accountability works, it is necessary to focus instead on national elections and the national political environment. Through a detailed, multimethod analysis this book establishes rigorously the paths of European accountability at the national level, its propitious contexts in the media and parliamentary debates, and whether the paths are similar from Greece to Germany. The findings have implications for both national and European Union democracy, underlining the importance that national institutions have in enabling citizens to hold the EU accountable.